CONTRIBUTION TO THE STUDY OF THE DEFORMATIONS OF EARTH DAMS’ BODIES. DAM OF THE H.P.P. OF SFIKIA, VERIA - Λουπασάκης Κ.; Χρηστάρας Β.; Δημόπουλος Γ.; Χατζηγώγος Θ. (Bulletin of the Geological Society of Greece, 2004)
This paper presents the numerical analysis procedure and the results arising from the simulation of the earth dam’s body of the hydroelectric power plan of Sfikia. This dam was simulated for its response during the staged construction of the body and during the gradual filling of the lake. This dam was selected because of the availability of specialized laboratory tests data coming from the materials of every zone. This selection was also enhanced by the availability of displacement and piezometric recordings coming from in situ instruments. Those data gave us the opportunity to control and to improve the numerical analysis procedure by means of numerous parametric analyses